Dynamic flow imaging using 320-detector row CT and motion coherence analysis in coronary aneurysms associated with Kawasaki disease. (14th December 2017) - Shimomiya, Yamato; Nagao, Michinobu; Yamasaki, Yuzo; Shirasaka, Takashi; Kondo, Masatoshi; Kojima, Tsukasa; Nishie, Akihiro; Yamamura, Kenichiro; Honda, Hiroshi
Abstract: Introduction: We propose a new dynamic flow imaging using 320-detector row CT, and investigate the assessment of coronary flow in aneurysms of Kawasaki disease in adulthood. Methods: Six patients with Kawasaki disease and coronary aneurysms associated (26.7 years old) and six controls were enrolled. Dynamic coronary CT angiography with 320-row CT was continuously performed at mid-diastole throughout 15–25 cardiac cycles with prospective Electrocardiogram gating after injection of contrast media. Dynamic data sets of 15–25 cycles were computed into 90–100 data sets by motion coherence image processing. Next, time–density curves for coronary arteries were calculated for all the phases. On the basis of the maximum slope method, coronary flow index was defined as the ratio of the maximum upslope of the attenuation of coronary arteries to the upslope of the attenuation of ascending aorta on the time–density curves. Coronary flow indexes for the proximal and distal sites of coronary arteries and intra-aneurysm were measured.